Loyalty system development based on blockchain technology - Petrović, Sara; Bjelica, Daniel; Radenković, Božidar (E-business technologies conference proceedings, 2021)
The subject of this paper is a development of a loyalty system based on blockchain technology. The theoretical section of this paper will analyze different types of loyalty programs, their advantages and disadvantages as well as the current market situation. The concepts of blockchain technologies and the possibilities of applying blockchain in the implementation of loyalty programs will be explored in detail. Also, the possibilities of blockchain integration, mobile and IoT technologies for the realization of loyalty programs in smart environments will be analyzed. In the practical section of this paper, a system of partner loyalty program as a smart city service will be designed and implemented. The Hyperledger Fabric development environment will be used to implement the blockchain component of the system. The implementation will be carried out in microservice architecture. An Android mobile application will be developed for user interaction with the platform.